(untitled) (Research, Society and Development, 2021)
The virus that spreads the COVID-19 was discovered in cases of viral pneumonia in Wuhan (China), in 2019, and was named SARS-CoV-2, by the World Health Organization (WHO) on January 12, 2020. The virus belongs to a large family of viruses consisting of individual positive RNA connected with an envelope, it has an N (Nucleocapsid) protein, generally conserved among β-coronaviruses, constantly used as a diagnostic tool for COVID-19. The MedTest Coronavirus (COVID-19) Ag (Rapid Test) is intended to qualitatively detect the presence of the virus, and the MedTest Coronavirus (COVID-19) IgG/IgM (Rapid Test) has the purpose of detecting IgG antibodies and IgM for COVID-19. The present study aimed to describe the profile of the results obtained in the rapid testing for COVID-19 in a pharmacy chain with branches in a city in the Southwest of Bahia, Brazil. This was a field research, with the indirect participation of 241 people who took the tests, aged between 18 and 60 years. The results were collected and compared later with the symptoms reported by the patients through a questionnaire applied before each test. Thus, by performing the two tests, and comparing the results with the symptoms described by the patients, a relationship between the test result, symptom and patient age was obtained. Based on the results, it was found that patients who presented symptoms of fever and loss of taste were more associated with the positivity of the antigen test, and the symptom of sore throat had a lower correlation with the positivity for the same test. It was possible to verify the presence of positivity for COVID-19 in asymptomatic patients, and the importance of performing the antigen and antibody tests in due time.